A questão da informação estratégica no ensino superior: os pecados informacionais e barreiras na comunicação da informação para a tomada de decisão na Universidade Estácio de Sá - Starec, Cláudio (2003)
This work upholds the premise that the mapping of the flow of information in an educational institution, such as Estácio de Sá University – Campi Nova América and Rebouças, hereafter called university, needs to be viewed as a competitive strategy due to the significant role that information plays today. The aim of this research was to identify the strategic value of information in an organization focused on education. The problems, noises and barriers in the communication of information and the effect they have on the making of decisions in the university was also discussed. Actually, what would managers like more than the use of meaningful information for decision making? And what would be more desirable for those in the management position of a university than having quick access to clear, objective, precise and current information whenever they need it? The Competitive Intelligence appears to give prominence to the issue of information as a strategic tool in the university and, possibly, as the most important one to help the managers of the university to make academic and administrative decisions not only in time, but also in real time. This dissertation comprises empirical research based on the experience of the author and field research carried out by a group of managers of the university, which helped to understand the thinking of the university manager on the question of the relevance of the information for the decision making. The chosen model to map the flow of information was the Mandala of the Scientific Spreading developed by Paul Caro. Among the conclusions reached in this paper, we pointed that the relevance of information in the perception of the managers is unique. Therefore, it should be considered a priority